Engaging on nationality status of non-Muslims: a maqasid-based approach - Haneef, Sayed Sikandar Shah (World League Organisation, 2010)
The non-Muslims resident of a Muslim state was accorded a special kind of citizenship known dhimmah in the past. Under this designation non-Muslims enjoyed full protections under the law in spite of constant state of hostilities between Dar al-Islam and Dar al-Harb. With the demise of Islamic Caliphate System after the First World War and constitutional collapse of the underlying principles behind dhimmah, its retention or redefinition became a subject of intense polemics among the legal scholars. By and large, the discourse followed two trends: traditional and reformist. The former regards this issue as permanently fixed, as detailed by classical jurists, while the latter views it as historically conditioned and thus changeable part of the Shari'ah. Practically modern Muslim states today accord equal citizenship to both their Muslim and non-Muslim population. At the academic level, however, this issue still seems unsettled. Even some leading contemporary thinkers, hesitate to engage with the issue in question beyond the traditional paradigm. Accordingly, this paper attempts to stimulate academic discussion on the issue which may somewhat contribute to the emergence of some kind of consensus among the jurists in future forums.